IHTIKÂR DAN DAMPAKNYA TERHADAP DUNIA EKONOMI - Muslim, Moch Bukhori (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2012)
There are some economic transactions that prohibited by religion because they only give benefit for one party. They are gambling, riba, fraudulence, (al-ghabn), tadlîs practice in buying and selling and hourding (ihtikâr). Therefore, it needs sence of transendence in every economical transaction. Ihtikâr is the economic activity undertaken by an economic agent with a hoard of goods in order to get maximum profit without seeing another person distress. Inthis case, the government should keep the market system which includes prohibiting ihtikâr, so the economic system can move with normal speed and full fairnessDOI: 10.15408/aiq.v4i1.2538